(untitled) (Medico Legal Update, 2020)
Background: Nephrotic syndrome in children is a common disease in the world, and is a group of clinical symptoms and include (loss of protein in the urine, low protein level in the blood, the accumulation of fluid in the body or edema, and high blood lipids). The cause of Nephrotic Syndrome is unknown. Neutrophil gelatinase associated lipocalin is a protein encoded in humans by the LCN2 gene. NGAL interferes with natural immunity by blocking iron, causing the growth of germs to be reduced. It is expressed in kidney, prostate, respiratory and digestive cells. NGAL is used as a vital guide to kidney injury. Method: Neutrophil gelatinase-associated lipocalin concentration was measured in blood plasma using enzyme-linked immunosorbent assay (ELISA) and urine NGAL by Abbott i1000, measured plasma and urine level of NGAL in 20 patients with steroid resistance nephrotic syndrome,20 patients with steroid sensitive nephrotic syndrome, 17 patients with early diagnosed nephrotic syndrome compare with 20 healthy volunteers enlisted as normal controls. Results: Urine NGAL and plasma NGAL are significantly increase in SRNS, SSNS, EDNS compared with control group. Conclusion: NGAL can be used to diagnostic biomarker to predict steroid Sensitive or steroid resistance in children with Nephrotic syndrome (NGAL is a differentiating marker between SSNS and SRNS).